2017
DOI: 10.1002/ps.4745
|View full text |Cite
|
Sign up to set email alerts
|

Grafting on resistant interstocks reduces scion susceptibility to pear psylla, Cacopsylla bidens

Abstract: Susceptibility to pear psylla decreased significantly following grafting of commercial Spadona on resistant interstock. This is the first demonstration of increased resistance to pear psylla conferred by the use of resistant interstock in pear trees and among the few examples demonstrating transfer of resistance to insects from the interstock in fruit trees. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Interstock had a positive effect on solving grafting incompatibility (SOSNA and KORTYLEWSKA, 2013;GIRARDI and FILHO, 2006;AGUS and EKA, 2017), stimulating dwarfing (DI VAIO et al, 2009;AN et al, 2017) and increased productivity (GIL-IZQUIERDO et al, 2004). More recently, interstock is able to increase tolerance to biotic stress (ERTI and AGUS, 2018;SHALTIEL-HARPAZ et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interstock had a positive effect on solving grafting incompatibility (SOSNA and KORTYLEWSKA, 2013;GIRARDI and FILHO, 2006;AGUS and EKA, 2017), stimulating dwarfing (DI VAIO et al, 2009;AN et al, 2017) and increased productivity (GIL-IZQUIERDO et al, 2004). More recently, interstock is able to increase tolerance to biotic stress (ERTI and AGUS, 2018;SHALTIEL-HARPAZ et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge there are no studies describing the influence of grafting on phloem chemistry of Prunus species, but it has been shown that rootstock species influences plant growth and fruit quality (Melnyk 2017 ). The rootstock-scion interaction can also influence psyllid feeding behavior, as grafting on resistant interstocks reduced scion susceptibility to pear psylla, Cacopsylla bidens (Shaltiel-Harpaz et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resistant selections “760” and “701” were tested as interstock with the commercial cultivar (“Spadona”) as the scion. These interstock grafts produce and export metabolites to the tree canopy that appear to confer resistance to C. bidens nymphs (Shaltiel-Harpaz et al 2018).…”
Section: Pest Managementmentioning
confidence: 99%